A educação de jovens e adultos/eja e ensino de geografía em Uberlândia-MG,2003 - Fernanda Borges Neto Benevides; Vânia Rúbia Farias Vlach (Sociedade & Natureza)
Education is considered a basic element for hte construction of a fairer and equalitarian society. In recent years, a relatively large return of yauths and adult people to schools in Brazil is being observed. In this work we had the objective to know the deveopment of the teaching/learning process of Geography, in classes of Education of younths and Adult People, of a non-regular teaching - the teaching to students who dropped school and returned to it some years later - of the elementary scholl. For that, a bibliographical research on the subject was done, which was related to the teaching for younths and adult people; later, a specific research was done, regarding the teaching of Geography above mentionde. Weekly observations in a 5th grade class, 'ensino compacto' - the students are allowed to return to scholl to conclute their studies in a shorter period of time - of the evening period int the Escola Municipal profa. Cecy Cardoso, in Uberlândia - MG, 2003. It was verified, among other results: 1) Absence of relationship between the Geography content taught in the school and the students' daily practice. In other words non-consideration of the student´s previous knowledge; 2)Shortage of appropriate didactic material to the public´s age, being evidenced the use of children didactic material which was tedious and not very attractive. Conclusions point out that the public request defferentiated and appropriate educational mehods, emphasizing the student´s previous and real knowledge, accomplishing connections among the Geography content taught in the school and the kowledge acquired by their life experiences.